Disputed diagnosis of scabies. - Milano, A. (European Journal of Pediatric Dermatology, 2015)
Sometimes the history of the mother and physical examination do not lead to the same diagnosis, as in this case in which we saw in the child skin lesions reminiscent of scabies in the absence of itching. Then you have to choose if you give more value to one or the other. In this case we gave more value to physical examination even in the absence of a classic history and despite the negativity of fresh examination for mites, using the ex adiuvantibus criterion that confirmed our diagnosis. Being wise after the event, we believe that the child or the mother had been infected in the hospital; the parents underwent specific therapy but the error consisted in not even treating the child attributing his lesions to other causes. The contemporary therapy of all family members who have had an intimate contact is one of the cornerstones of scabies therapy; the latter must be clearly explained to the parents (1, 2).